A review on biological methodologies in municipal solid waste management and landfilling: Resource and energy recovery. (December 2022) - Saravanan, A.; Kumar, Ponnusamy Senthil; Nhung, Tran Cam; Ramesh, B.; Srinivasan, S.; Rangasamy, Gayathri
Abstract: Rapid industrialization and urbanization growth combined with increased population has aggravated the issue of municipal solid waste generation. MSW has been accounted for contributing tremendously to the improvement of sustainable sources and safe environment. Biological processing of MSW followed by biogas and biomethane generation is one of the innumerable sustainable energy source choices. In the treatment of MSW, biological treatment has some attractive benefits such as reduced volume in the waste material, adjustment of the waste, economic aspects, obliteration of microorganisms in the waste material, and creation of biogas for energy use. In the anaerobic process the utilizable product is energy recovery. The current review discusses about the system for approaching conversion of MSW to energy and waste derived circular bioeconomy to address the zero waste society and sustainable development goals. Biological treatment process adopted with aerobic and anaerobic processes. In the aerobic process the utilizable product is compost. These techniques are used to convert MSW into a reasonable hotspot for resource and energy recovery that produces biogas, biofuel and bioelectricity and different results in without risk and harmless to the ecosystem. This review examines the suitability of biological treatment technologies for energy production, giving modern data about it. It likewise covers difficulties and points of view in this field of exploration. Highlights: Review Highlights. Effect of municipal solid waste on human and the environment is inspected. Factors limiting the aerobic composting process have been comprehensively discussed. Biological treatments for energy recovery from MSW were discussed. Roadmap for circular economy using waste to energy techniques is proposed.